1953
DOI: 10.1017/s0022029900007044
|View full text |Cite
|
Sign up to set email alerts
|

Section B. Bacteriology and mycology applied to dairying

Abstract: Reviews of the progress of dairy sciencepreformed enzymes, are added to chemically defined substrates, giving clear-cut results. A clockwork automatic bacteriological inoculating device has been devised by Fuson & Marcus (20). An ingenious device(2i), patented in the U.S.A., for counting bacterial colonies, consists of a fountain pen connected to an electro-magnetic counter which registers each time the pen touches the Petri dish or roll-tube. Hannay (22) has described a new type of laterally illuminated colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1954
1954
1968
1968

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 285 publications
0
1
0
Order By: Relevance
“…aerogenes were most frequently encountered in Thomas's studies of ropy milk(U6,ll7), in which water supplies were found to be the chief source of the organisms. Sundman's work (118,119) confirms that of Jones in part, since she demonstrated the protein character of a slime produced by strains of Str. cremoris from Finnish ropy sour milk, differing from the polysaccharide slime produced by Str.…”
Section: Defectsmentioning
confidence: 75%
“…aerogenes were most frequently encountered in Thomas's studies of ropy milk(U6,ll7), in which water supplies were found to be the chief source of the organisms. Sundman's work (118,119) confirms that of Jones in part, since she demonstrated the protein character of a slime produced by strains of Str. cremoris from Finnish ropy sour milk, differing from the polysaccharide slime produced by Str.…”
Section: Defectsmentioning
confidence: 75%